Proton therapy in pediatric neuro-oncology. Potential advantages and the relationship between cost and results - O. S. Regentova; O. I. Shcherbenko; E. V. Kumirova; F. F. Antonenko; V. A. Solodkiy (Сибирский онкологический журнал, 2024)
The aim of study: to analyze the accumulated experience and try to identify those clinical situations in which the use of protons will be economically and clinically more effective than photon radiation therapy. Material and methods. The articles devoted to the study of the evaluation and comparison of the effectiveness of proton and photon radiation beams in the treatment of tumors of the central nervous system and published over the past 25 years were searched in the Medline, Embase and the Cochrane Library databases. Results. the analysis of available publications has shown that accelerated protons do not improve survival rates and disease-free rates in all forms of brain tumors compared with photon therapy. However, protons can significantly increase the level of dose distribution conformity and reduce the dose to critical structures (pituitary gland, cochlea, eye lenses, hypothalamus), thus reducing the risk of hearing and visual impairment as well as hormonal and cognitive disorders. All this is critically important for potentially curable malignant tumors, such as medulloblastoma and germinoma, for low malignant potential tumors (grade 1–2 glioma) or tumors with decreased metastatic potential, since proton therapy compared to photon therapy reduces the risk of late side effects that worsen the quality of life of cured children. Conclusion. central nervous system tumors are one of the most common solid malignant neoplasms in children. Radiation therapy (RT) is recognized as an important therapeutic component of treatment and is often used in strategies for multimodal therapy of tumors of the central nervous system in children. Proton radiation therapy is one of the attractive methods of radiotherapy with minimal dose distribution to normal tissues and a decrease in the absorbed dose. The precision of protons reduces the risk of long-term side effects associated with this type of treatment and the induction of secondary malignancies, which is of particular importance for the quality of life.